APPROACHING TO THE 250TH ANNIVERSARY OF THE SCIENTIFIC CENTER OF CHILDREN'S HEALTH - A. A. Baranov; S. A. Sher; V. Y. Albitskii (Union of pediatricians of Russia, 2013)
This article is dedicated to the life of professor Vera Pavlovna Lebedeva - head of the maternity and childhood protection (MCP) department at the RSFSR People's Commissariat of Health and one of the founders of the first State scientific maternity and childhood protection institute (SSMCPI) - a predecessor of the USSR AMS Institute of pediatrics. In the 1930s the SSMCPI was named after Lebedeva. This article gives documental archive data, Lebedeva's scientific works, articles from pediatric magazines,  colleagues' memoirs which reflected the main milestones of her life and professional activity, theoretical-and-practical and pedagogical in particular. Thanks to V.P. Lebedeva's initiative and activity, the virtually new state MCP system was created in the USSR and the first national scientific institution of a pediatric profile was organized.